Cyberpunk and the Ethics of Technological Futures: Exploring the Human-Machine Nexus and Dystopian Realities - Pooja Dahiya; Sneha Sharma; Omdev Dahiya (The Bioscan, 2026)
This research examines cyberpunk as a complex textual space containing values and aesthetics related to techno- futures and changing human-machine relations. In addition to this engagement with ethical questions regarding posthuman technologies in human society, this study is situated within a larger debate regarding the changing role of technology in social life and its cultural, moral, and existential implications on postindustrial societies. This research interrogates the defining or constitutive elements of cyberpunk narratives, particularly the dystopian imaginings of techno-futures, corporate hegemony, and social stratification as representing the consequences of unconstrained technological growth and the opportunities for techno-human symbiosis, neural and somatic augmentation, and the socio-psycho-technical sensibilities for interaction. This research expands on this antagonism by examining technological representationalism in cyberpunk to weigh the potential rewards of technology against ethical considerations of use. The study further iterates cyberpunk’s valuing critique of the values of privacy, autonomy, and ecological sustainability, and the disintegrating boundaries between the material and the virtual. Through an examination of representation in literature and film, this study lays the groundwork for understanding cyberpunk as a model or lens for understanding how technology is developing in today’s contemporary paradigms of societal emergence. In the end, this research illuminates how cyberpunk urges audiences to confront existential dilemmas and consider the promises and threats of the integration of technology in every facet of human life.